2014
DOI: 10.1016/j.mrfmmm.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dNTP pool alterations on fidelity of leading and lagging strand DNA replication in E. coli

Abstract: The fidelity with which organisms replicate their chromosomal DNA is of considerable interest. Detailed studies in the bacterium Escherichia coli have indicated that the fidelity of leading- and lagging-strand DNA replication is not the same, based on experiments in which the orientation of certain mutational targets on the chromosome was inverted relative to the movement of the replication fork: different mutation rates for several base-pair substitutions were observed depending on this orientation. While the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
9
0
3
Order By: Relevance
“…However, we have no such explanation for the twofold bias for A:T transitions to occur when A is on the LGST, although we speculated that DNA polymerase was more likely to insert a C opposite A when the A was templating lagging-strand synthesis (Lee et al 2012). In contrast, other studies have indicated that leading strand DNA synthesis is more error-prone than lagging strand synthesis (Gawel et al 2014). The results presented here with a strain defective for both MMR and Ndk support our original hypothesis, suggesting that lagging-strand synthesis is more error prone, at least when C is misinserted opposite template A or T. However, the mutational spectrum seen in the absence of MMR is the result of replication errors that are not corrected by the proofreader.…”
Section: Discussionmentioning
confidence: 63%
“…However, we have no such explanation for the twofold bias for A:T transitions to occur when A is on the LGST, although we speculated that DNA polymerase was more likely to insert a C opposite A when the A was templating lagging-strand synthesis (Lee et al 2012). In contrast, other studies have indicated that leading strand DNA synthesis is more error-prone than lagging strand synthesis (Gawel et al 2014). The results presented here with a strain defective for both MMR and Ndk support our original hypothesis, suggesting that lagging-strand synthesis is more error prone, at least when C is misinserted opposite template A or T. However, the mutational spectrum seen in the absence of MMR is the result of replication errors that are not corrected by the proofreader.…”
Section: Discussionmentioning
confidence: 63%
“…It is well documented that dNTP pool imbalances affect the rate and spectrum of spontaneous mutation, presumably by driving preferential incorporation of the nucleotide(s) in excess (59,63). The potential effects of proportional increases or decreases in dNTP levels on DNA polymerase fidelity could also be predicted from kinetic considerations and have been demonstrated in a few biochemical studies (64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in both ndk and dcd were used in a recent study by Gawel et al (9), who asked whether DNA replication fidelity in E. coli is higher on the leading or lagging strand. Even though in bacteria both strands are replicated by the same polymerase, previous studies had suggested that fidelity is higher for lagging‐strand replication, a seemingly counterintuitive finding because of the more complex process of discontinuous DNA synthesis on the lagging strand.…”
Section: Mutagenic Mechanisms Inferred From Nucleotide Pool Variationsmentioning
confidence: 99%